Novel RRM2B Mutation and Severe Mitochondrial DNA Depletion: Report of 2 Cases and Review of the Literature - Kropach, Nesia; Shkalim-Zemer, Vered; Orenstein, Naama; Scheuerman, Oded; Straussberg, Rachel (Neuropediatrics, 2017)
Purpose To describe the clinical presentation and implications of mitochondrial DNA depletion disorder of two siblings with early fatal encephalomyopathy and a novel mutation in the RRM2B gene. The relevant literature is reviewed.Methods We describe two brothers aged 2.5 months and 1 month, respectively, who were hospitalized in a tertiary pediatric medical center for evaluation of focal seizures, hypotonia, poor feeding, failure to thrive, lactic acidosis, and developmental delay. The older brother also had seizures, and the younger had severe bilateral neurosensory deafness.Results Genetic sequencing of the RRM2B gene revealed the same novel mutation in both the siblings. Both children died due to respiratory failure at ages 3 and 2.5 months, respectively.Conclusion The combination of neonatal hypotonia, developmental delay, and lactic acidosis should raise a clinician's suspicion of a mitochondrial depletion disorder and prompt further genetic studies.
Keywords: RRM2B gene mutation; hypotonia; elevated lactate; deafness; seizures; tubulopathy